Food styling trends in Malaysia: elevating culinary experiences with visual artistry / Noorsa Riza Johari ... [et al.] - Johari, Noorsa Riza; Bahari, Khairil Anuar; Ibrahim, Mohd Zool Fadli; Din, Norrina (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Food styling has become an art form in the culinary industry that goes beyond simply presenting delicious foods. It is the art of visually enticing food presentation, which improves the overall eating experience and captivates guests with its creativity. With its many cultural influences and rich culinary tradition, Malaysia has embraced the trend of food styling and infused creativity and innovation into its culinary offerings. This article explores the development of trend food styling in Malaysia, its primary goals, and its effects on the local culinary scene. This article explores the development of trend food styling in Malaysia, its primary goals, and its effects on the local culinary scene.